Cloning, expression, purification and crystallization of Schizosaccharomyces pombe Set7, a putative histone methyltransferase - Mevius, Damiaan E. H. F. (Acta Crystallogr F Struct Biol Commun, 2016)
Dysfunction of histone-modifying enzymes affects chromatin regulation and is involved in carcinogenesis, tumour progression and other diseases. Histone methyltransferases are a family of key histone-modifying enzymes, but their structures, functions and mechanisms are incompletely understood, thus constraining drug-design efforts. Here, preliminary steps towards structure–function studies of Schizosaccharomyces pombe Set7, a putative histone methyltransferase and the first yeast full-length SET-domain-containing protein to be studied using X-ray crystallography, are reported. The methods from cloning to X-ray diffraction and phasing are discussed and the results will aid in prospective studies of histone-modifying enzymes.